2019
DOI: 10.1109/access.2019.2937219
|View full text |Cite
|
Sign up to set email alerts
|

Matching Real-World Facilities to Building Information Modeling Data Using Natural Language Processing

Abstract: Building Information Modeling (BIM) is a promising technology for building informatics. Currently, an increasing number of applications adopt BIM to improve the building operations and facility management. In these applications, matching real-world facilities to the corresponding BIM items is a fundamental yet challenging task. This study addresses this issue using Natural Language Processing. Firstly, a novel BIM hierarchy tree (HiTree) is proposed to model the original spatial structure relationships of a BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Furthermore, we also observed that most of the highly cited studies such as [12], [13], [45], [56]- [58], [60] are published in the top two countries (China and United Kingdom). [10], [13], [20], [47], [48], [50], [56]- [59][30], [31], [39], [41] 14…”
Section: ) Geographical Distribution Of the Selected Studiesmentioning
confidence: 99%
“…Furthermore, we also observed that most of the highly cited studies such as [12], [13], [45], [56]- [58], [60] are published in the top two countries (China and United Kingdom). [10], [13], [20], [47], [48], [50], [56]- [59][30], [31], [39], [41] 14…”
Section: ) Geographical Distribution Of the Selected Studiesmentioning
confidence: 99%
“…Machine learning (ML) is a field in the domain of artificial intelligence (AI) [ 10 ] that focuses on providing machines (robots) with learning abilities like humans. ML has various eminent applications in the areas of medical treatment [ 11 ], speech recognition [ 12 ], natural language processing (NLP) [ 13 , 14 ], image processing and signal processing [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the threshold of using the BIM object database for practitioners and the general public, Wu et al (2019)proposed a retrieval engine for BIM object database, which mainly retrieved and recommended component-level information. Xie et al (2019) proposed a method of matching real-world facilities to BIM data, which is also on component-level. The BIM model contains information of the whole life cycle of the building.…”
Section: Introductionmentioning
confidence: 99%